Prescription patterns of diclofenac in patients with cardiovascular diseases or at high risk for cardiovascular diseases at primary health care level in Montenegro: retrospective, national, drug utilization study - Stanković, Maja; Turković, Nemanja; Dobrić, Silva; Rančić, Nemanja (Vojnosanitetski pregled, 2023)
Background/Aim. Diclofenac, a non-selective inhibitor of cyclooxygenase with analgesic, anti-inflammatory, and antipyretic effects, is one of the most prescribed nonsteroidal anti-inflammatory drugs (NSAIDs). The aim of this study was to analyze the prescription patterns of diclofenac systemic formulations at primary health care (PHC) level in Montenegro, in patients with cardiovascular (CV) diseases (CVD) and patients with risk factors for CVD, from 2016 to 2020. Methods. A retrospective national drug utilization study was conducted and it included patients with CVD, to whom prescribing diclofenac was contraindicated, and patients with risk factors for CVD, to whom diclofenac could be prescribed but with increased precaution. PHC information system has been used as a source of medical data for these patients. Results. Within the observed period, prescribing diclofenac systemic formulations, dominantly oral formulations in 75 mg dose, increased by 36.9% [from 4.6 of defined daily doses (DDD) /1,000 inhabitants/day in 2016 to 6.3 DDD/1,000 inhabitants/day in 2020]. A rising trend in prescribing diclofenac was also recorded in patients with CVD or those with risk factors for CVD, to whom diclofenac prescribing is contraindicated. Out of the overall number of patients who were prescribed diclofenac in 2016, 2017, 2018, 2019, and 2020, 16%, 18%, 24%, 15%, and 20% of them, respectively, already had a CVD or some risk factor for CVD. Most CV patients (39.7%), for whom the use of diclofenac was contraindicated, had ischemic heart disease and were prescribed 40.7% of the total amount of diclofenac prescribed for this group of patients (expressed in DDD/1,000 inhabitants/day for the given medicine). The majority (77.4%) of CV patients to whom the drug could be prescribed, but with increased precautions, had hypertension, and they were prescribed 77.2% of the total amount of diclofenac prescribed for this group of patients (expressed in DDD/1,000 inhabitants/day for the given medicine). Conclusion. Despite the undertaken regulatory measures aimed at a safer prescription of diclofenac to patients with CVD or at high risk of developing CVD, this medicine is still widely prescribed at the level of PHC in Montenegro, even in cases that represent a contraindication for its use.